2017
DOI: 10.21059/buletinpeternak.v41i1.12727
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diet Containing High Alpha-Linolenic Acid on Omega-3 Fatty Acids and Health Status of the Heart in Broilers

Abstract: The objective of the study was to examine the effects of diet containing high alpha-linolenic acid (ALA) on omega-3 long chain polyunsaturated fatty acids (n-3 LCPUFA) and the health status of heart in broilers. Diets were based on a commercial starter diet, with a low level of fat. The experimental diets contained two levels of ALA (2.23 and 19.37%), with the total fat content was approximately 5%. Pure or blended vegetable oils were included at a level of 2.8% in order to produce diets with the desired level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…The content of n-3 PUFA in the cardiac tissue seems not to be only determined by its respective dietary percentage, but also the presence of n-6 PUFA in the diet (the dietary n-6:n-3). Therefore, although the canola oil diet provided a considerable proportion of n-3 PUFA (6.6%), this diet did not elevate the n-3 PUFA content in the cardiac tissue because it was still accompanied by a high dietary n-6:n-3 ratio (4.09) in agreement with Kartikasari, et al [63] finding. Further, Gregory et al [51] , demonstrated that a canola diet, but not a tallow based diet, enriched the phospholipid class of the cardiac lipids with certain n-3 PUFA, specifically the total of EPA and DHA.…”
Section: Heartsupporting
confidence: 87%
See 1 more Smart Citation
“…The content of n-3 PUFA in the cardiac tissue seems not to be only determined by its respective dietary percentage, but also the presence of n-6 PUFA in the diet (the dietary n-6:n-3). Therefore, although the canola oil diet provided a considerable proportion of n-3 PUFA (6.6%), this diet did not elevate the n-3 PUFA content in the cardiac tissue because it was still accompanied by a high dietary n-6:n-3 ratio (4.09) in agreement with Kartikasari, et al [63] finding. Further, Gregory et al [51] , demonstrated that a canola diet, but not a tallow based diet, enriched the phospholipid class of the cardiac lipids with certain n-3 PUFA, specifically the total of EPA and DHA.…”
Section: Heartsupporting
confidence: 87%
“…Indeed, the influence of dietary fat type on the fatty acid composition of broiler chicken tissues (in particular meat) has been investigated for decades . In addition, broiler chickens of different strains respond differently to dietary fats and the fatty acid profile of chicken tissues reflects both the ingested and the in vivo synthesised fatty acids . Many trials have associated a significant improvement in broiler performance with dietary fats that differ in fatty acid composition …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, relatively higher amounts of antioxidants present in sunflower oil attenuated the oxidative damage of heart muscles thereby resulted comparatively better RV:TV. Partly consistent results were reported in a previous study where increasing proportions of alpha-linolenic acid (ω-3) in broiler diet had no significant effect on RV:TV (Kartikasari et al, 2017).…”
Section: Cardio-pulmonary Morphometrysupporting
confidence: 90%
“…The FA composition of this tissue was not measured but warrants further discussion as a measure of avian heart health. Dietary ALA has been shown to increase poultry heart LC n-3 PUFA composition although there were no differences in more functional assays such as ventricle mass ratio [26].…”
Section: Discussionmentioning
confidence: 99%